PENELITIAN GROUNDED THEORY, APAKAH ITU..? - V. J. Wisnu Wardhono (Bina Ekonomi, 2011)
Generally speaking, Grounded Theory is an approach for looking systematically at (mostly) qualitative data (like transcripts of interviews or protocols of observations) aiming at the generation of theory. Sometimes, Grounded Theory is seen as a qualitative method, but Grounded Theory reaches farther:  it combines a specific style of research (or a paradigm) with pragmatic theory of action and with some methodological guidelines. This approach was written down and systematized in the 1960s by Anselm Sfrauss  (himself a student of Herbert Blumer) and Bamey Glaser  (a student  of Paul Lazarsfeld), while working  together  in studying  the sociology  of t7lness at the University of California. For and with their studies, they developed a methodology, that was then made explicit and became the founding stone for an important  branch of qualitative sociology.  Important concepts of Grounded Theory are categories, codes and codings.  The research principle behind Grounded Theory is neither inductive nor deductive, but combines both in a way of abductive reasoning (coming from the works of Charles S. Peirce). This leads to a research practice where data sampling, data analysis and theory development are not seen as distinct and disjunct, but as different steps  to be repeated until one can describe  and explain the phenomenon that  is to be researched.  This stopping point is reached when new data doesn’t change the emerging theory anymore. Grounded Theory according to Glaser emphasizes induction or emergence, and the individual researchers creativity within a clear frame of stages, while Sfrauss is more interested in validation criteria and a systematical approach.  This methodical way of creating Grounded Theory (and still be acceptable to scientific standards)  is explained  in Strauss/Corbin (1990).